A critical discourse analysis of Tom Lembong’s pleidoi in the context of his corruption case - Avvena Sanit; Hanafi Wibowo; M. Rizky Fadhil (Linguistics Initiative, 2026)
This study investigates how ideological legitimacy and claims of innocence are discursively constructed in Tom Lembong’s handwritten pledoi as reported by Tirto.id within the context of his corruption case. While previous Critical Discourse Analysis (CDA) research on corruption has primarily examined media framing and political elites, limited attention has been given to technocratic actors and to defense statements as autonomous sites of ideological production. Addressing this gap, the study employs a qualitative research design with a descriptive–interpretive orientation, utilizing Teun A. van Dijk’s CDA framework to analyze the discourse at macrostructural, superstructural, and microstructural levels. The data consists of a single online news article reproducing the pledoi during the pre-trial phase. The findings indicate that the global meaning of the text is structured around themes of gratitude, cooperation with legal authorities, institutional trust, nationalism, and religious devotion, which collectively construct an ideology of moral–patriotic integrity. At the superstructural level, the discourse follows a coherent narrative sequence that moves from respectful address and gratitude to moral self-positioning, institutional alignment, national commitment, and religious closure, guiding readers toward an interpretation centered on humility and ethical credibility. At the microstructural level, positive lexicalization, inclusive pronouns, high-commitment modality, presuppositions of innocence, repetition, politeness markers, and the absence of legal jargon contribute to a non-adversarial and morally persuasive discourse. Overall, the pledoi functions as an ideological substitute for legal defense, foregrounding moral, national, and religious values to negotiate legitimacy under conditions of legal and institutional asymmetry. This study contributes to CDA by foregrounding defense discourse as a site of ideological construction and by extending corruption discourse analysis to technocratic actors within Indonesian digital journalism.